Applicability of the use of waste from different banana cultivars for the cultivation of the oyster mushroom - Carvalho, Cristiane Suely Melo de; Aguiar, Lorena Vieira Bentolila de; Sales-Campos, Ceci; Minhoni, Marli Teixeira de Almeida [UNESP]; Andrade, Meire Cristina Nogueira de [UNESP] (Sociedade Brasileira de Microbiologia, 2012)
The objective of this research was to evaluate the oyster mushroom Pleurotus ostreatus- (Jacq.: Fr.) Kumm. cultivation in substrates based on different combinations of wastes (leaf, pseudo-stem and pseudo-stem + leaf) and banana cultivars - Musa spp. (Thap Maeo, Prata Anã, Pelipita and Caipira) during 49 days. Organic matter loss in the substrate by action of the fungus was also evaluated during that period. It was verified that the pseudo-stem waste provided the best averages of biological efficiency among all cultivars tested and best rates were obtained by Thap Maeo (61.5%). The highest organic matter loss (OML) was obtained from pseudo-stem + leaf wastes (Prata Anã - 78.6%; Thap Maeo - 67.6%; Pelipita - 64.8%; Caipira - 60.6%). Therefore, the use of those wastes showed itself viable for P. ostreatus cultivation due to its availability and low cost, besides decreasing discards to environment.
Keywords: Pleurotus ostreatus; mycelium; organic matter; biological efficiency; supplementation